2018
DOI: 10.5483/bmbrep.2018.51.9.020
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation ofHOXBcluster genes are epigenetically regulated in tamoxifen-resistant MCF7 breast cancer cells

Abstract: Tamoxifen (TAM) is commonly used to treat estrogen receptor (ER)-positive breast cancer. Despite the remarkable benefits, resistance to TAM presents a serious therapeutic challenge. Since several HOX transcription factors have been proposed as strong candidates in the development of resistance to TAM therapy in breast cancer, we generated an in vitro model of acquired TAM resistance using ER-positive MCF7 breast cancer cells (MCF7-TAMR), and analyzed the expression pattern and epigenetic states of HOX genes. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Moreover, the small clinical study on 22 patients has suggested benefit of this practice even in the determination of response to a chemotherapy 31 . Further, epigenetics is now understood to play big role in determination of drug sensitivity in breast cancer 32 , even in the delicate balance between resistance and sensitivity to tamoxifen 3336 . This not only suggests that our work is timely, but also calls for further studies to improve our understanding of the underlying mechanisms, which can lead to much improved targeted therapies for the treatment of estrogen receptor-expressing breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the small clinical study on 22 patients has suggested benefit of this practice even in the determination of response to a chemotherapy 31 . Further, epigenetics is now understood to play big role in determination of drug sensitivity in breast cancer 32 , even in the delicate balance between resistance and sensitivity to tamoxifen 3336 . This not only suggests that our work is timely, but also calls for further studies to improve our understanding of the underlying mechanisms, which can lead to much improved targeted therapies for the treatment of estrogen receptor-expressing breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…HoxB genes are transcription factors involved in development [ 30 ] and whose activation is regulated by chromatin domain boundaries [ 31 , 32 ]. Recently, Hox genes have been shown to transcriptionally activate EGFR in drosophila [ 33 ] and breast cancer cells [ 34 ], although their role in EGFR-driven lung tumors is largely uncharacterized. Among other significant domains, we found several cancer-associated genes.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings discovered the interaction of HOXA5 with HOXB6 and HOXB7 . The downregulation of HOXA5 increased the expression of HOXB6 and HOXB7, which were associated with poor clinical outcomes in cancer patients [ 83 , 84 , 85 ]. On the other hand, the hypermethylation of ADHFE1 further reduced the expression of neighbouring proteins, ADH6 , ADH7, as well as ADH1A, in which the genes were associated with the patient’s prognosis and cancer pathogenesis [ 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%